Analisis Peran Guru Pendamping Anak Berkebutuhan Khusus Tipe Slow Learner dalam Pembelajaran Kelas 1 di SD Muhammadiyah 2 Socah - Julia Ayu Puspita; Nova Estu Harsiwi (Universitas 45 Surabaya, 2024)
In this world, a child cannot choose what kind of circumstances he will be born into, some are born normal and there are also those who are destined to be born with special features. Children with this privilege are usually called children with special needs (ABK). Even though it is said that children with special needs still deserve the same services and treatment as children in general, especially in seeking education, which currently has an inclusive education program. Inclusive education is an education delivery system that provides students with special needs the opportunity to participate in learning in the same environment as normal children who usually need special assistance according to their type. Many people don't know how important the role of accompanying teachers is in the smooth running of learning. So research was carried out which aimed to determine the role of accompanying teachers in the learning process, especially the type of slow learner class 1 at SD Muhammadiyah 2 Socah. This research uses a descriptive qualitative approach, using observation, interviews and documentation as data collection techniques. Then you will get results in the form of the role of accompanying teachers for ABK students, and analysis of the learning activities carried out. From this research it can be concluded that accompanying teachers have a very important role in the student learning process and learning activities which include planning, implementation processes, and assessment of students.